Search Halal Products Using BM25F and the Analytic Hierarchy Process - Rakhmawati, Nur Aini; Fajriyadi, Adnan Mauludin (JEPIN (Jurnal Edukasi dan Penelitian Informatika), 2019)
In Indonesia, the Institute of Food and Drug Administration (LPPOM) MUI is the official institution that provides information about halal products.Â  However, the lack of information is provided on the website. Halal Nutrition Food is an application that has a function to facilitate the search for halal products that are incorporated in an integrated database in the form of Linked Open Data. To improve the searching features, we exploit BM25F. BM25F can process structured documents such as instances in RDF. The BM25F return the answer based on four fields: product name, manufacturer name, product ID and ingredient name. The weight of each field is calculated using the Analytic Hierarchy Process (AHP) where the product name gets the highest weight value. The number of keywords and the keywords occurrences influence the score of query results.